2012
DOI: 10.1152/jn.00574.2011
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge impact in low-magnesium model of seizure in rat hippocampus

Abstract: Putative mechanisms of induction and maintenance of seizure-like activity (SLA) in the low Mg(2+) model of seizures are: facilitation of NMDA receptors and decreased surface charge screening near voltage-gated channels. We have estimated the role of such screening in the early stages of SLA development at both physiological and room temperatures. External Ca(2+) and Mg(2+) promote a depolarization shift of the sodium channel voltage sensitivity; when examined in hippocampal pyramidal neurons, the effect of Ca(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 52 publications
2
37
1
1
Order By: Relevance
“…Both cellular depolarization and hyperpolarizing shift of the voltage-gated channel activation cause similar effects on neuronal network activity due to reduced voltage difference between the resting membrane potential and potentials where Na + -channels are activated. Removal of Mg 2+ ions from extracellular solution shifts leftward the half activation and facilitates the amplitude of I Na compared with the 1mmol Mg 2+ solution [12].Our results suggest that the change in the surface charge dramatically affects the probability of induction of low-Ca 2+ SLA, providing evidence that Mg 2+ can reduce cerebral excitability by screening surface charge and support the idea that lack of Mg 2+ could cause epileptic seizures. In previous studies, it was shown that manipulations with surface charge could alter the pattern of epileptiform like activity [19].…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Both cellular depolarization and hyperpolarizing shift of the voltage-gated channel activation cause similar effects on neuronal network activity due to reduced voltage difference between the resting membrane potential and potentials where Na + -channels are activated. Removal of Mg 2+ ions from extracellular solution shifts leftward the half activation and facilitates the amplitude of I Na compared with the 1mmol Mg 2+ solution [12].Our results suggest that the change in the surface charge dramatically affects the probability of induction of low-Ca 2+ SLA, providing evidence that Mg 2+ can reduce cerebral excitability by screening surface charge and support the idea that lack of Mg 2+ could cause epileptic seizures. In previous studies, it was shown that manipulations with surface charge could alter the pattern of epileptiform like activity [19].…”
Section: Resultssupporting
confidence: 69%
“…In previous studies, it was shown that manipulations with surface charge could alter the pattern of epileptiform like activity [19]. In previous work we demonstrated that surface charge plays a crucial role in lowMg 2+ model of epilepsy [12].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations